Brand’s Cool Dimension Effect on Customer Satisfaction and Its Implication to Visual E-WoM - Trihadi Pudiawan Erhan; Purnamaningsih Purnamaningsih; Nosica Rizkalla (Universitas Multimedia Nusantara, 2019)
As Word of Mouth (WOM) progress as one of the most potent marketing instruments, millennials are a vital contributor to the growth of eWOM. Considering how powerful eWOM is and the significance of millennials as the generation that derives the transformation of eWOM as the primary source of information for the customer, it is important to know the variables that drive millennial customers desire to provide information about product and service through their own social media account. This study then employed structural equation modeling to analyze the data. This study finds that out of the two, cool factors only hedonic cool is proven to have a positive and significant influence on customer satisfaction. The other finding is that active Visual eWOM activity of customer are positively influenced by customer satisfaction.